Efecto del abono orgánico en el cultivo de la soya glycine max, variedad iniap 307 - Campoverde Gallardo, Dario Alexander (2006)
In the Finca Campoverde, located in the parish The Change belonging to the canton Machala, county of The Gold, the application of organic payments was studied in the cultivation of the soya INIAP 307 (Glycine max.). The objectives outlined for this project were the following ones: 1. to determine the effectiveness of the organic payments in the soya production INIAP 307, 2. to Select the organic payment and dose but adapted in the soya production, 3. to Carry out the economic analysis. For the investigation of the work the following treatments were applied: Biol(Liquido) with 18,24 l/ha, worm Humus with 30,4 kg/ha, Bokashi with 30,4 kg/ha, Vitagres with 6,1 l/ha, Compost with 72.96 kg and the witness that any treatment was not applied. The products were applied in parcels fixed at random in a design in blocks with four repetitions, totalling 24 experimental units. During the development of the cultivation she/he was given such cultural works respectively as watering and their control fitosanitario. The products were applied directly to the floor and by means of aspersions foliares, among the organic payments that it was used we have, those of application to the floor that you/they are: Bokashi, worm Humus and Compost. As for the liquid payments: Biol and Vitagres that were applied with a bomb CP3 by means of a previous calibration of the aspersion volume and the dose of the corresponding payments. The corresponding variables were evaluated: Days to the emergency, Height of the plant at the 30, 60, 90 days, Days to the floración, Days to the maturation and fructificación, I Number of sheaths for plant, Weight of 100 seeds, Yield kg/ha and Plagues and illnesses. The statistical analyses, threw great significancia in the height from the plant to 60 90días, for what the organic fertilizers reached their bigger productive capacity of the soya. The best weight corresponded the Bokashi with 19,5 g, followed by the Humus with 19,2 g, with regard to the witness that was the but I lower. The treatments Bokashi, Humus and Compost reached the best yields respectively with 4360,9 , 4293,9 and 4193,4 kg/ha.